Market Microstructure Effects of Government Intervention in the Foreign Exchange Market - Bossaerts, Peter; Hillion, Pierre (Review of Financial Studies, 1991)
An asymmetric information model of the bid–ask spread is developed for a foreign exchange market subject to occasional government interventions. Traditional tests of the unbiasedness of the forward rate as a predictor of the future spot rate are shown to be inconsistent when the rates are measured as the average of their respective bid and ask quotes. Larger bid–ask spreads on Fridays are documented. Reliable evidence of asymmetric bid–ask spreads for all days of the week, albeit more pronounced on Fridays, are presented. The null hypothesis that the forward rate is an unbiased predictor of the future spot rate continues to be rejected. The regression slope coefficients increase toward unity, however, indicating a less variable risk premium.